2021
DOI: 10.33774/chemrxiv-2021-01pw7-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bonding character, electron delocalization, and aromaticity of cyclo[18]carbon (C18) precursors, C18-(CO)n (n = 6, 4, and 2): Focusing on the effect of -CO groups

Abstract: Although the unique cyclo [18]carbon (C 18 ) realized by recent experiments has been greatly concerned, it has so far remained elusive. In contrast, its precursors C 18 -(CO) n (n = 6, 4, and 2), which can be separated stably, are of more practical significance. In this paper, the bonding character, electron delocalization, and aromaticity of the C 18 -(CO) n (n = 6, 4, and 2) with out-of-plane and in-plane dual π systems (π out and π in ) perpendicular to each other are studied by combining quantum chemical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…For corresponding Cartesian coordinates, please refer to the supplementary material of Ref. [28]. All precursors are observed to be strictly planar, and molecules with n = 2, 4, and 6 belong to C 2v , C 2v , and D 3h point groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For corresponding Cartesian coordinates, please refer to the supplementary material of Ref. [28]. All precursors are observed to be strictly planar, and molecules with n = 2, 4, and 6 belong to C 2v , C 2v , and D 3h point groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The geometric structures and excitation characteristics of the C 18 -(CO) n (n = 2, 4, and 6) were respectively obtained by DFT and time-dependent DFT (TD-DFT) calculations at ωB97XD [29]/def2-TZVP [30] level in the gas phase. Our recent theoretical work has demonstrated that this computational strategy can reproduce the crystal structure of C 18 -(CO) 6 well, so it is considered to be competent to describe the present systems [28]. The molecular (hyper)polarizabilities were calculated by both analytic derivatives of the system energy [namely, coupled-perturbed Kohn-Sham (CPKS)] and finite field (FF) methods at the ωB97XD/aug-cc-pVTZ(-f,-d) level, where aug-cc-pVTZ(-f,-d) is a reduced version of the aug-cc-pVTZ basis set [31] with the removal of f-type polarization functions of non-hydrogen atoms and d-type polarization functions of hydrogen atoms.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometric structures and excitation characteristics of the C 18 -(CO) n (n = 2, 4, and 6) were respectively obtained by DFT and time-dependent DFT (TD-DFT) calculations at ωB97XD [29]/def2-TZVP [30] level in the gas phase. Our recent theoretical work has demonstrated that this computational strategy can reproduce the crystal structure of C 18 -(CO) 6 well, so it is considered to be competent to describe the present systems [28]. The molecular (hyper)polarizabilities were calculated by both analytic derivatives of the system energy [namely, coupled-perturbed Kohn-Sham (CPKS)] and finite field (FF) methods at the ωB97XD/aug-cc-pVTZ(-f,-d) level, where aug-cc-pVTZ(-f,-d) is a reduced version of the aug-cc-pVTZ basis set [31] with the removal of f-type polarization functions of non-hydrogen atoms and d-type polarization functions of hydrogen atoms.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In the past two years, various theoretical studies involving the properties, [17][18][19][20][21][22][23][24][25][26][27][28] behaviors, [29][30][31][32][33] and potential applications [34][35][36][37] of C 18 and its analogues and derivatives have been carried out by several research groups. Among these, the theoretical design of supramolecular complex by Jiang et al showed that C 18 can be hosted inside the [11]CPP through intermolecular π-π interaction, [35] emphasizing the potential of C 18 as a building block to construct molecular devices by residing in carbon materials of suitable size and shape.…”
Section: Introductionmentioning
confidence: 99%